The Construction of Resistance in the Lyrics of the Song “Bayar Bayar Bayar” by The Band Sukatani - Ahmad Mubarok; Khaerudin Imawan; Novicky Alban Adiputra (Dialogika : Jurnal Penelitian Komunikasi dan Sosialisasi, 2026)
This study analyzes the creation of meanings of resistance and social criticism in the lyrics of the song "Bayar Bayar Bayar" by the band Sukatani, which went viral in the Indonesian digital public sphere. This study uses Roland Barthes's semiotics approach to interpret the meanings on the three levels of denotation, connotation, and myth. The data in this study were song lyrics, which were qualitatively analyzed with a descriptive-interpretive method. At the denotative level, it refers to the practice of "paying" in various activities involving the police. On the connotative level, repetition of "pay" suggests the idea that extortion has become an informal mechanism that is already established and practiced between society and the police. The myth level indicates the normalization of social reality, which is perceived as a practice of extortion that is common, and not usually critically examined. The phenomenon of viral popularity of "Bayar Bayar Bayar" affirms that music is the space of symbolic resistance that articulates the public's dissatisfaction with the abuse of power and violation of public rights. This study adds a value to communication and semiotics research in which song lyrics have become a space for producing meaning, social criticism and ideology in the digital sphere.